Study of Deritis Ratio in Acute Myocardial Infarction Patients in a Tertiary Care Hospital - Marasini, Surendra; Sah, Sanjay Kumar; Gupta, Suprita; Jha, Amit Chandra; Yadav, Nirdhan; Karn, Achutanand Lal; Sah, Sanjay Kumar; Yadav, Tapeshwor; Gurmaita, Raman Kumar (Med Phoenix, 2024)
Introduction: The ratio of Aspartate Aminotransferase (AST) to the Alanine Aminotransferase (ALT) is known as the Deritis ratio. Many studies have highlighted, the significance of AST and ALT measurement as a prognostic significance in cardiovascular diseases including acute myocardial infarction. The current study aimed to discuss the correlation of Creatine Kinase MB (CKMB) and Cardiac Troponin I with the Deritis ratio in the retrospectively enrolled Nepalese population. Materials and Methods: Two hundred and sixty-four (264) cases of acute myocardial infarction who had undergone AST and ALT measurement were enrolled for the study by non-probability purposive sampling technique. The study variables are AST, ALT, CKMB, Troponin I, age, etc. The above-mentioned variables were measured by using a fully automatic clinical chemistry analyzer Beckmann Coulter AU480 after proper quality control check and calibration. Results: Out of 264 patients, 162 were male and 102 were female. There was no significant difference in age (P value: 0.54) and Deritis ratio (P value: 0.73) between the male and female genders when the mean and standard deviation were compared. The non-parametric correlation (Spearman’s rho) analysis revealed the positive correlation of Deritis ratio with the cardiac troponin I (0.18, 0.00) which is statistically significant. Secondly, the Deritis ratio was positively correlated with the CKMB (0.40, 0.00) which was statistically significant. Conclusion: Our results have shown the raised Deritis ratio in acute myocardial infarction patients, which represents the release of AST during the myocardial infarction or the stress to the hepatocytes due to the hemodynamic changes occurring during myocardial infarction.